2007
DOI: 10.1080/11038120601094732
|View full text |Cite
|
Sign up to set email alerts
|

Housing matters in very old age—yet differently due to ADL dependence level differences

Abstract: In order to support the development of optimal housing options for older people, we need to increase our understanding of relations between aspects of housing and aspects of health in old and very old age. The objective of this cross-sectional study was to explore whether and how aspects of housing are related to life satisfaction and perceived health among very old, single-living Swedish people. Based on survey study data from the ENABLE-AGE Project (n = 397), correlation and regression analyses were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 35 publications
4
58
1
Order By: Relevance
“…This is probably important among very old persons and a strong reason for staying put at home when disability, frailty, and comorbidity increase. Results from the ENABLE-AGE Survey Study show that the experience of home as meaningful has been found to be related to experience of health (23,24). One of the studies (24) of very old people living in Sweden, Germany, Great Britain, Hungary, and Latvia found that the participants who experienced home as meaningful and useful were more independent in daily activities and perceived a greater sense of well-being.…”
Section: Discussionmentioning
confidence: 96%
“…This is probably important among very old persons and a strong reason for staying put at home when disability, frailty, and comorbidity increase. Results from the ENABLE-AGE Survey Study show that the experience of home as meaningful has been found to be related to experience of health (23,24). One of the studies (24) of very old people living in Sweden, Germany, Great Britain, Hungary, and Latvia found that the participants who experienced home as meaningful and useful were more independent in daily activities and perceived a greater sense of well-being.…”
Section: Discussionmentioning
confidence: 96%
“…We used the data gathered in Sweden and Germany as part of the ENABLE-AGE Project (Iwarsson et al 2007a, b) to test our hypotheses. The primary reason for this is that participants were drawn at random from official national registers in a highly similar way in Sweden and Germany.…”
Section: Design and Study Samplementioning
confidence: 99%
“…On the one hand, the results indicated that both subjective and objective aspects of housing should be considered in order to understand the relationships of the environment, healthy ageing, and ''ageing in place''. On the other hand, it was concluded that much is still to be learned about the complex interplay of home environment and health along the process of ageing and that qualitative studies in this area are needed to fine-tune the debate on housing arrangements for older individuals with ADL dependence [15].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in recent studies [10,15,16] the theoretical ideas of the P-E fit model were used as a framework for empirical explorations of relationships between aspects of objective and perceived (i.e., some subjective aspects of) housing, ADL, and ageing, among old unimpaired community dwellers. On the one hand, the results indicated that both subjective and objective aspects of housing should be considered in order to understand the relationships of the environment, healthy ageing, and ''ageing in place''.…”
Section: Introductionmentioning
confidence: 99%